German Unification : Economic Issues Occasional Paper No. 75. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
This paper discusses comparison of economic and social indicators in the year 1988 between Federal Republic of Germany (FRG) and German Democratic Republic (GDR). The budgetary costs of unification will be substantially larger than initially envisaged. Moreover, if one adds to the budget the increases in government debt related to equalization paper, a portion of the old enterprise debt on the books of the banks. The Trust Fund has been assigned a task or enormous scope and complexity: the privatization, restructuring, and in some cases, liquidation of 8000 enterprises with 4 million employees. Even taking care of the short-run financial problems of these enterprises has proved daunting; the more fundamental task will be near impossible to achieve with any rapidity. It is clearly essential to the success of economic integration that capital allow east rather than labor flowing west and that income growth and new opportunities arc enough to meet reasonable aspirations on the pan of the residents of East Germany.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet